The Diversification of Sea Processed Products to Increase Fishermen's Income in Brondon Village, Lamongan Regency - Aini Hidayati, Nur; Purmiyati, Atik; Dyah Hendrawati, Lucy (Pelita Masyarakat, 2025)
This community service activity aims to optimize the economic potential of marine catches in Brondong Village through product diversification assistance for micro-entrepreneurs which involves direct practice of processing mackerel fish into ready-to-eat food. Based on observations, it was found that even though the economic potential in this area is high, the community still uses traditional business patterns which results in low income for fishermen. The fundamental problem identified is the lack of processing of marine catches and product diversification. By using the Focus Group Discussion (FGD) method with a participatory approach to identify conditions, needs, problems and potential in village development. The results obtained from the pre-test assessment show that micro business actors' knowledge regarding product diversification is still low, with an average score of 65. However, after the training, there was a significant increase, where almost 90% of participants obtained a post-test score above 80 These results show that this mentoring activity has succeeded in increasing the knowledge and skills of micro business actors in diversifying seafood products, which is expected to increase fishermen's income and the welfare of the Brondong Village community.